THE INFLUENCE OF GOVERNANCE ON FOOD LOSS AND WASTE: A TANZANIAN PINEAPPLE VALUE CHAIN PERSPECTIVE - Kanyangemu, Anna; Waized, Betty; Turuka, Florens (Applied Studies in Agribusiness and Commerce, 2026)
Food loss and waste remain a substantial challenge in agricultural value chains, particularly in developing countries. This study examines the influence of governance of food loss and waste within the pineapple value chain in Tanzania. Using qualitative methods, data were collected in Dar es Salaam. Geita, Morogoro, and Pwani regions through focus group discussions, interviews, and observations. The study mapped actors and explored the role of governance, power dynamics, and coordination, drawing on resource dependence and institutional theories to explain how actor relationships, power imbalances, and institutional influences shape food loss and waste. Three types of governance structures were revealed- Spot market, captive, and relational structures, affecting food loss differently. In the captive governance structures, pre-finance arrangements lock farmers into selling only to specific traders, often leading to significant on-farm losses when market conditions shift. Spot markets, on the other hand, generate losses when harvested fruits do not meet the informal standards set by buyers, such as size, ripeness, and other physical attributes, due to limited market information. Weak coordination, information asymmetry, and power imbalances among value chain actors contribute to substantial food loss and waste. Main challenges faced by farmers include poor access to markets, financial constraints, and weak bargaining power. Institutional gaps, including weak regulatory frameworks and inadequate support from government and private sector, exacerbate inefficiencies. The study emphasizes that governance plays a central role in shaping food loss and waste. Strengthening farmers’ associations, improving market linkages, and addressing institutional gaps are critical for reducing food loss and waste and increasing value chain resilience.